Stephen Neill's Anglicanism: An Anglican Classic - Sachs, W. L. (Journal of Anglican studies, 2007)
Stephen Neill's Anglicanism has been the classic book on Anglican history and tradition for a generation. Books which become classics endure because they exhibit timeless features. Neill's Anglicanism succeeds because he delineates core features of the church's tradition which originated in English circumstances and spread beyond them. The book's endurance also reflects its comprehensive narrative and objectivity. For Neill English precedent left an enduring mark without enshrining English authority. Anglicanism's genius has been its capacity to embrace local variations of expression. Yet Neill foresaw the tensions inherent in post-colonial Anglicanism. The irony of the church's adaptability and growth was the resulting strain on its consensual forms that began in his lifetime. Local variety would extend to a degree that would erode over-arching consensus and strain the structures which would enforce it, as Neill saw plainly.